Disrupting environmental crime at the local level: an operational perspective. Issue 1 (December 2017) - Barrett, Stoyan; White, Rob
Abstract The multi-dimensional nature of environmental crimes requires innovative means to combat them. This paper examines the nature and dynamics of one particular collaborative law enforcement approach directed at environmental crime. While much interest in multi-agency and multi-pronged approaches has been generated in recent years, especially as this pertains to environmental crime at the international and regional levels, this paper provides a detailed description of how this can occur at the local level. Based on a case study of nefarious activities relating to illegal waste management in Durham and surrounding areas (located in the North East of England), the paper emphasises the importance of 'disruption' as an important operational concept, and how inter-agency cooperation under skilled leadership and with clear purpose can lead to tangible enforcement outcomes. As the article demonstrates, particular agencies on their own have limited impact and do not always address the issue of how to take away an organised criminal group's ability to function. By contrast, multi-agency work enables authorities to work in a united front and thus to succeed in disrupting criminal activities causing environmental harm.